The distribution shifts of Pinus armandii and its response to temperature and precipitation in China - Xiaofeng Zheng; Pengxiang Gao; ShuoXin Zhang (PeerJ, 2017)
Background The changing climate, particularly in regard to temperature and precipitation, is already affecting tree species’ distributions. Pinus armandii, which dominates on the Yungui Plateau and in the Qinba Mountains in China, is of economic, cultural and ecological value. We wish to test the correlations between the distribution shift of P. armandii and changing climate, and figure out how it tracks future climate change. Methods We sampled the surface soil at sites throughout the distribution of P. armandii to compare the relative abundance of pollen to the current percent cover of plant species. This was used to determine possible changes in the distribution P. armandii. Given the hilly terrain, elevation was considered together with temperature and precipitation as variables correlated with distribution shifts of P. armandii. Results We show that P. armandii is undergoing change in its geographic range, including retraction, a shift to more northern areas and from the upper high part of the mountains to a lower-altitude part in hilly areas. Temperature was the strongest correlate of this distribution shift. Elevation and precipitation were also both significantly correlated with distribution change of P. armandii, but to a lesser degree than temperature. Conclusion The geographic range of P. armandii has been gradually decreasing under the influence of climate change. This provides evidence of the effect of climate change on trees at the species level and suggests that at least some species will have a limited ability to track the changing climate.